Active layered localization method for dynamic muti-sinks wireless sensor networks - HAN Peng; WU Hua-feng; REN Jiu-chun; GAO Chuan-shan (Tongxin xuebao, 2007)
An active layered localization method was proposed.The method was event-driven and divided into two layers（sensor layer and sink layer）.The method not only supported the movement of nodes,but also reduced the localization cost of sensors and extended the network lifetime.